Maritime transportation and people mobility in the early diffusion of COVID-19 in Croatia - Cot, Corentin; Aksentijević, Dea; Jugović, Alen; Cacciapaglia, Giacomo; Mannarini, Gianandrea (Frontiers in Public Health, 2023)
The outbreak of COVID-19 in Europe occurred in early 2020. During the year, several waves of infection developed with different timings across the European countries. The onset of the largest wave of infection occurred in August-September. Croatia is a hotspot of tourism in the Mediterranean region, and thus may have acted as an incubator of the pandemic during the summer of 2020. Given this, we designed a data-driven investigation to assess the possible role of the mobility of passengers to and within Croatia through various modes of transportation. To this end, observational datasets were integrated with the modelling framework of the "epidemic Renormalisation Group". Comparing the models to the epidemiological data allowed to disfavour, in the case of Croatia in 2020, any prominent role in propagating the infection by either maritime or train transportation, while highlighting the leading role of both road and airborne mobility. The proposed framework aims to test hypotheses regarding the causation of infectious waves, with the capacity to rule out unrelated phenomena.